Measuring and Analyzing the Impact of Foreign Direct and Private Investment on Iraq's GDP for the Period (2004-2019) - sadiq, Jafar; Hajji, Ismat; Kovan , Abdullah (Humanities Journal of University of Zakho, 2022)
The study's goal is to determine the influence of FDI and private investment had on Iraq's GDP from 2004 to 2019. The (Eviews10) model was created using an analytical descriptive technique and a typical quantitative approach. Through the Augmented Dickey-Fuller Test application, the unit root test was used to determine the degree of integration of variables for the purpose of selecting the estimate model, as well as the detection of common integration using the GDP boundary test approach as a child variable and variables. The study revealed that independent variables (FDI, public and private investment), and therefore, assessing the long- and short-term connection using (ARDL) self-regression models, explained 86 percent of the changes in the dependent variable (GDP).